2022
DOI: 10.3390/buildings12101532
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Consumption in Higher Education Buildings in Thailand during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic forced higher education institutions to switch to online learning for most of 2020 and 2021 for the safety of their students and staff, which significantly impacted campus resource consumption. This study aims to analyze the changes in electricity consumption in higher education buildings based on comparisons of three academic years to understand more about the energy implications of the post-COVID-19 era. The electricity data were collected from 181 samples of the electricity meter recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…During that time many factories, universities, and offices in Bangkok and surrounding provinces were closed. Figure 5a indicates that the measure of the demand drop compared with respect to the previous year's demand shows that the peak demand was reduced approximately by 2000 MW, and can be considered similar to the COVID-19 pandemic lockdown [22,51]. Each year, there is a noticeable decrease in electricity demand during holidays and special events.…”
Section: Seasonal and Holiday Patternmentioning
confidence: 86%
“…During that time many factories, universities, and offices in Bangkok and surrounding provinces were closed. Figure 5a indicates that the measure of the demand drop compared with respect to the previous year's demand shows that the peak demand was reduced approximately by 2000 MW, and can be considered similar to the COVID-19 pandemic lockdown [22,51]. Each year, there is a noticeable decrease in electricity demand during holidays and special events.…”
Section: Seasonal and Holiday Patternmentioning
confidence: 86%
“…In other study, Chaloeytoy et al (2022) found that switching to the online learning mode significantly decreased electricity consumption in higher education facilities in Thailand. Samuels et al (2021) also found that the impact of COVID-19 on the EU of schools in South Africa results show a substantial reduction ranging between 30% and 40% during the hard lockdown.…”
Section: Introductionmentioning
confidence: 85%
“…During that time many factories, universities, offices in Bangkok and surrounding provinces were closed for a few months. Figure 5a indicates that the measure of the demand drop compared with respect to previous year's demand, shows that the peak demand was reduced approximately by 2000MW and can be considered the similar stage of Covid-19 lockdown situation [36,56]. Each year, there is a noticeable decrease in electricity demand during holidays and special events.…”
Section: Seasonal and Holiday Patternmentioning
confidence: 92%